Methyl Gallate Suppresses the Migration, Invasion, and Epithelial-Mesenchymal Transition of Hepatocellular Carcinoma Cells via the AMPK/NF-κB Signaling Pathway in vitro and in vivo - Liang, Huaguo; Chen, Zexin; Yang, Ruihui; Huang, Qingsong; Chen, Hongmei; Chen, Wanting; Zou, Li; Wei, Peng; Wei, Shijie; Yang, Yongxia; Zhang, Yongli (Frontiers in Pharmacology, 2022)
Methyl gallate (MG), a polyphenolic compound found in plants, is widely used in traditional Chinese medicine. MG is known to alleviate several cancer symptoms. However, most studies that have reported the antitumor effects of MG have done so at the cellular level, and the inhibitory effect and therapeutic mechanism of MG in hepatocellular carcinoma (HCC) have not been extensively explored in vivo. We aimed to understand the therapeutic mechanism of MG in HCC in vitro and in vivo. MTT and colony formation assays were used to determine the impact of MG on the proliferation of a human HCC cell line, BEL-7402; wound healing and transwell assays were used to quantify the migration and invasion of HCC cells. Western blotting was used to quantify the expression of the AMPK/NF-κB signaling pathway proteins. In vivo tumor growth was measured in a xenograft tumor nude mouse model treated with MG, and hematoxylin–eosin staining and immunohistochemistry (IHC) were used to visualize the histological changes in the tumor tissue.We found that MG showed anti-proliferative effects both in vitro and in vivo. MG downregulated the protein expression of AMPK, NF-κB, p-NF-κB, and vimentin and upregulated the expression of E-cadherin in a dose-dependent manner. Additionally, MG inhibited the migration and invasion of HCC cells by decreasing MMP9 and MMP2 expression and increasing TIMP-2 expression. These were consistent with the results of IHC in vivo. MG inhibited the proliferation, migration, and invasion of HCC cells. This effect potentially involves the regulation of the AMPK/NF-κB pathway, which in turn impacts epithelial-mesenchymal transition and MMP expression.